Utilization of drug in patients admitted with abnormal uterine bleeding in a tertiary care teaching hospital - Govindasamy, Dhivya; Karunakaran, Padmavathi; Ramesh, Rajalakshmi; Paramasivamsasanger, Kamalavarshini; Ponnusamy, Rajalakshmi (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The objective of the study was assessing utilization of drug in patients admitted with Abnormal Uterine Bleeding in a tertiary care teaching hospital. Methods: The observational study was conducted at Department of Obstetrics and Gynecology, Rajah Muthiah Medical College and Hospital, Annamalai University, Annamalai Nagar, Tamil Nadu, from the period of July 2019 to September 2019. A total 30 gynecology patients were included. Results: A total 30 patients most of the patients were between the age groups of 36-45 years 66.6%. The most common clinical condition AUB and co-morbidities condition were 19 (63.3%). The majority of patient were prescribed with ferrous sulfate 27 (90%). The defined daily dose (DDD) per patient for norethisterone 36 followed by ferrous sulfate 23.11. The average number of drugs per prescription 10.8, percentage of drug prescribed in generic name 69.56% and number of drugs prescribed from NLEM-2015 86.95%, number of drugs prescribed from EDL-2019 were 69.56% and percentage of prescription with antibiotic 80%, percentage of prescription with injection 70%. Conclusions: This study has shown the utilization of drugs prescribed in AUB patient. The most commonly prescribed drug was ferrous sulfate and most prescribed antifibrinolytic drug was tranexamic acid for treating AUB.